2009
DOI: 10.1093/jpepsy/jsp029
|View full text |Cite
|
Sign up to set email alerts
|

Description of a Standardized Nutrition Classification Plan and its Relation to Nutritional Outcomes in Children with Cystic Fibrosis

Abstract: Adoption of a standardized approach to nutritional assessment and treatment led to significant improvement in nutritional outcomes of CF patients, demonstrating that systematic changes in clinical practice can improve clinical outcomes substantially over a short period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Indeed, published literature indicates that improvements diminish with time and the median follow-up for intervention was 1 year 8 10. Our study confirms the findings of another CF centre in which there was a relative improvement in median BMI by 19% in 15 months 17. At Lurie Children's the relative improvement in mean BMI percentile improved 30.8% and in the same time frame, UAB/COA had a relative improvement of 18.5%.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, published literature indicates that improvements diminish with time and the median follow-up for intervention was 1 year 8 10. Our study confirms the findings of another CF centre in which there was a relative improvement in median BMI by 19% in 15 months 17. At Lurie Children's the relative improvement in mean BMI percentile improved 30.8% and in the same time frame, UAB/COA had a relative improvement of 18.5%.…”
Section: Discussionsupporting
confidence: 86%
“…Educational and behavioral interventions resulted in increasing adherence to PERT and increasing caloric intake as well . Two studies reported adopting a standard approach to nutritional assessment and treatment . This led to significant improvement in nutritional outcomes of patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…15 Two studies reported adopting a standard approach to nutritional assessment and treatment. 16,17 This led to significant improvement in nutritional outcomes of patients with CF. Our standardized approach in addition to regular evaluation (and additional evaluation as needed) to address the nutritional needs of the patients resulted in achieving our goal of improvement in median BMI in our CF Center similar to other studies Lung function, although not a primary outcome of our project, was evaluated to determine if the gains in BMI percentile in the lower groups corresponded to improvement in lung function.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,31,32 We found that a low BMI was associated with a higher CF-SPS score. On average our participants had a BMI well below the recommended 50th percentile.…”
Section: Discussionmentioning
confidence: 59%
“…These included the various symptom parameters that were used in defining a PEx 7,16,17,20,[26][27][28] and CF PRO, 21,29,30 as well as factors involved in CF lung disease and nutrition. [4][5][6]8,[31][32][33] The various existing questionnaires and scoring systems in CF such as the CFQ-RRSS and the CFRSD were also reviewed. 34 Since this survey was being designed to be used regularly with patients, only items that could be reasonably reported by patients (or their proxy) were considered.…”
Section: Part 1: Survey Developmentmentioning
confidence: 99%